Sosialisasi Transaksi Dompet Digital Dana ke Masyarakat Kelurahan Bangun Jaya, Kota Pagar Alam - Nurmaleni Nurmaleni (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2024)
This community service activity aims to socialize the use of the DANA digital wallet to the people of Bangun Jaya Village, Pagar Alam City. The methods used are presentations, demonstrations and direct practice. The results of the activity show an increase in public understanding and interest in using the DANA digital wallet for daily transactions. Using the Dana Digital Wallet will save the community IDR 6,500 more, compared to using other Digital Wallets.